Pelatihan Microsoft Excel Sebagai Penunjang Ketrampilan Hard Skill Bagi Siswa SMK - Fitriana Harahap; Saragih, Nidia Enjelita; Adawiyah, Robiatul; M. Rizky (Publikasi Pengabdian Masyarakat, 2022)
The Tridharma of Higher Education contains three important points, namely education, research and community service. One way to implement the tridharma of higher education is to do community service. Community service on this occasion was carried out with the partner of SMK BM Budi Agung. In the digitalization era, children's creativity becomes very important, because it is necessary to provide computing programs such as Microsoft Office, one of which is Microsoft Excel. The need for education about computer applications regarding Microsoft Excel. Therefore, the solution offered is in the form of training that aims to make SMK students have the ability to understand Microsoft Excel, understand functions and can process numbers and make simple financial reports with Microsoft Excel. The final result of Community Service activities by evaluating learning outcomes. The results of this activity, students are able to process data with various formulas using Microsoft Office Excel 2010. This activity has a good impact on increasing Hard Skill Skills for Vocational Students.